Investigation of accumulation ability of crops in point of dynamics of residual quantities if copper-containing pesticides - N. E. Fedorova; M. V. Egorova; A. S. Rodionov; J. J. Bogdanova (Овощи России, 2022)
Relevance. Study of pesticide residues is an integral part of registration tests. It is present a particular interest in terms of hygienic safety of eating vegetable crops grown with use of protective agents.Methods. The analysis procedure includes an approach developed by the authors, based on microwave digestion of samples after cryo-destruction, followed by analysis by atomic absorption spectrometry with electrothermal atomisation. The approaches used in research, allow us to trace the dynamics of copper content in fruits of potatoes, tomatoes, cucumbers and onions, during the vegetation periods of 2020-2021 in different soil and climatic zones.Results. It is shown that treatment with copper-containing preparations does not affect the content of copper in fruits of the studied crops during the whole experiment, except for the day of sampling immediately after the treatment. At the same time, reliable excesses in comparison with control samples are observed in experiments, where the aboveground part of crops is investigated. For example, the content of copper in tomato fruits in 2020, taken on the day of the last treatment, was 0.61±0.16 mg/kg and 0.47±0.08 mg/kg in the experimental and control samples, respectively. In 2021, the trend continued and copper concentration on the day of treatment was 0.80±0.15 mg/kg and 0.64±0.12 mg/kg respectively in the experimental and control samples. In the study of onion treated with copper oxychloride-based preparation, the concentration of copper in the whole plant (leaves + bulb) on the day of treatment in 2020 was 8.5±1.1 mg/kg in the experimental sample and 0.43±0.18 mg/kg in the control sample. In 2021, the copper concentration in the experimental sample collected on the treatment day was 14.1±3.8 mg/kg and in the control sample was 1.1±0.2 mg/kg respectively.